Archaeology from the AIR. - ATHITAKIS, MARK (Humanities)
The article focuses on aviator Charles A. Lindbergh, who was the first person to make a solo transatlantic airplane flight with the "Spirit of St. Louis" monoplane in 1927. It mentions the photographs taken by Charles with his wife Anne Morrow during supervision of airfields in Arizona towns and adds that they are helping archaeologists study prehistoric ruins of Native American communities in the region.